Pharmacy students’ perceptions and satisfaction with blended instruction in quantitative chemical analysis course - Sonji, Ghassan; Hammoudi Halat, Dalal; Mourad, Nisreen; Sonji, Nada; Mehyou, Zeina; Rahal, Mohamad (Pharmacy Education, 2023)
Background: Course satisfaction in blended learning has become a priority among educators to keep students on track during their studies. This study investigated the Community of Inquiry (CoI) three key components, i.e. teaching, social, and cognitive presences and other factors that affect student satisfaction at Lebanese International University (LIU). Objective: The study aimed to examine pharmacy undergraduate students who enrolled in, and the effect of blended learning courses on learning environment perceptions, learning outcomes, and overall academic performance. Methods: Exactly 283 second-year students from a private School of Pharmacy registered in the Quantitative Chemical Analysis course participated in this study. Data were collected using an online survey, assessing students’ prior pre-pharmacy course experiences. Results: The majority of students (58%) commended the course content, organisation, teaching resources, course design, and clarity of directions. Course satisfaction significantly correlated with age and social, cognitive, and instructional presences (Spearman’s Rho: 0.739-0.750, p < 0.05). Discussion: Studies found that blended instruction can improve student engagement, satisfaction, and learning outcomes, which are influenced by the quality of online materials, communication, feedback, and the degree of student and instructor interaction. Conclusion: The outcomes of this study support the assumption that blended learning encourages active, in-depth, and self-directed learning.